Preventing suicide among older women in China: the integration of gamified group-based exercise in a virtual reality environment - Zhang, Jinjin (Frontiers in Psychology, 2025)
ObjectiveSuicide among elderly women has increasingly been recognized as a significant public health concern, necessitating the development of innovative, evidence-based interventions tailored to this vulnerable population. This study aimed to examine the effectiveness of gamified group-based physical activity in a virtual reality (VR) environment for enhancing psychological resilience and reducing suicidal ideation among elderly women.MethodsA randomized controlled trial (RCT) design with convenience sampling was adopted for this study. A total of 120 elderly women with clinically confirmed suicidal ideation were recruited through purposive announcements at senior care facilities in Beijing, China, and were then randomly allocated into experimental (n = 60) and control (n = 60) groups using a computer-generated randomization schedule. Data were collected using two validated questionnaires: the Subjective Vitality Scale and the Life Hope Questionnaire. The normality of data distribution was assessed using the Kolmogorov–Smirnov test, and the homogeneity of variances across groups was evaluated via Levene’s test. To control for baseline differences and assess the impact of the intervention, data were analyzed using analysis of covariance.ResultsThe findings revealed statistically significant improvements in both subjective vitality and life hope scores among participants in the experimental group compared to those in the control group (p < 0.01). The effect size for hopefulness was η2 = 0.29, and the effect size for mental vitality was η2 = 0.21.ConclusionThese findings highlight that gamified VR-based group exercise is a promising non-pharmacological approach for improving psychological well-being and mitigating suicide risk in elderly women. By combining immersive technology, social engagement, and motivational components, such interventions offer an effective, engaging, and scalable strategy to address mental health challenges in aging populations.